PENGARUH PERMAINAN DIGITAL MATCH UP PADA WEB INTERACTY.ME DALAM MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN PADA ANAK USIA 4-5 TAHUN DI TK AL FAJAR - Utami Nur Hakim; Cucu Sopiah; Andi Ali Kisai (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Early reading ability in children aged 4–5 years at TK Al Fajar still faces various challenges, such as difficulties in pronouncing syllables, recognizing letters, understanding simple words, and writing their own names. This condition indicates that the learning process is not yet optimal because the media used by teachers tends to be conventional, less innovative, and does not make sufficient use of digital technology. In the modern era, children are more familiar with technology, so it is necessary to develop innovative learning media that suit their characteristics. Therefore, this study aimed to analyze the effect of the digital game Match Up Interacty on improving early reading skills in young children. This study employed a quantitative approach with a pre-experimental design, specifically the one group pretest-posttest model. The research subjects were 31 students from group A at TK Al Fajar. Data were collected through early reading tests, which included letter recognition, syllable pronunciation, and simple word reading, as well as observations of the learning implementation. Data analysis was conducted using a paired sample t-test and N-Gain calculations to measure improvements after treatment. The findings revealed a significant difference between pretest and posttest scores, with most students showing improvements in their early reading ability. However, several students did not experience significant changes, and some even showed a decline. Overall, the Match Up Interacty media had a positive impact on enhancing early reading skills, although its effectiveness was not uniform across all students. This study suggests that educational digital games should be further developed with more diverse content and tested on larger populations to maximize their role in supporting children’s early literacy.